A rapid screening method for evaluating the total migratable hydrocarbons in paper products by headspace gas chromatography. Issue 18 (1st April 2019) - Dai, Yi; Zhu, Chuxing; Xue, Meigui; Chai, Xin-Sheng; Chen, Chunxia; Chen, Runquan; Hu, Huichao
Abstract : Herein, we report a rapid screening method for evaluating the hydrocarbon contamination in paper samples by headspace gas chromatography (HS-GC). Abstract : Herein, we report a rapid screening method for evaluating the hydrocarbon contamination in paper samples by headspace gas chromatography (HS-GC). This method was based on conducting the near-complete migratable release of hydrocarbons from a paper matrix to the headspace in 35 min at 98 °C. By programming the GC column temperature, other co-existing volatile organic compounds in the sample can be effectively separated from the migratable hydrocarbons. To simplify the method calibration, the concept of total migratable hydrocarbons was introduced and n -pentadecane was used as the standard hydrocarbon compound in the calibration. The results indicate that the present method offers good precision (the relative standard deviation < 9.8%) and accuracy (recovery between 94.3 and 101%). The present method can be a valuable tool for the quality assessment of total migratable hydrocarbons of paper products, aiming at providing a good guidance for safely using the recycled paper-based materials in various applications.